2021
DOI: 10.1111/nph.17613
|View full text |Cite
|
Sign up to set email alerts
|

Establishing asymmetry: stomatal division and differentiation in plants

Abstract: Summary In the leaf epidermis, stomatal pores allow gas exchange between plants and the environment. The production of stomatal guard cells requires the lineage cells to divide asymmetrically. In this Insight review, we describe an emerging picture of how intrinsic molecules drive stomatal asymmetric cell division in multidimensions, from transcriptional activities in the nucleus to the dynamic assembly of the polarity complex at the cell cortex. Given the significant roles of stomatal activity in plant respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…In the Arabidopsis stomatal lineage, cell polarity and cytoskeleton-mediated nuclear migration and ACDs are regulated by a different set of polarity genes ( Guo et al, 2021b ; Muroyama and Bergmann, 2019 ; Ramalho et al, 2022 ). Breaking of asymmetry in the stomatal lineage (BASL), a dicot-specific protein, serves as an intrinsic polarity factor to regulate ACDs of meristemoid mother cells and forms a polarity crescent distal to the division plane ( Dong et al, 2009 ; Nir et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Arabidopsis stomatal lineage, cell polarity and cytoskeleton-mediated nuclear migration and ACDs are regulated by a different set of polarity genes ( Guo et al, 2021b ; Muroyama and Bergmann, 2019 ; Ramalho et al, 2022 ). Breaking of asymmetry in the stomatal lineage (BASL), a dicot-specific protein, serves as an intrinsic polarity factor to regulate ACDs of meristemoid mother cells and forms a polarity crescent distal to the division plane ( Dong et al, 2009 ; Nir et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Arabidopsis stomatal lineage, cell polarity and cytoskeleton-mediated nuclear migration and ACDs are regulated by a different set of polarity genes (Guo et al, 2021a; Muroyama and Bergmann, 2019; Ramalho et al, 2022). BREAKING OF ASYMMETRY IN THE STOMATAL LINEAGE (BASL), a dicot-specific protein, serves as an intrinsic polarity factor to regulate ACDs of meristemoid mother cells (MMCs) and forms a polarity crescent distal to the division plane (Dong et al, 2009).…”
mentioning
confidence: 99%
“…BASL promotes polarisation of BREVIS RADIX (BRX) family proteins and POLAR LOCALIZATION DURING ASYMMETRIC DIVISION AND REDISTRIBUTION (POLAR) within its own polarity domain (Pillitteri et al, 2011; Rowe et al, 2019). The Arabidopsis polarity proteins can scaffold kinases to regulate cell division capacity, fate asymmetry and nuclear migration (Guo et al, 2021a; Muroyama and Bergmann, 2019). POLAR recruits the glycogen synthase kinase 3 (GSK3)-like kinase BIN2 to regulate cell division capacity (Houbaert et al, 2018), whereas a positive-feedback loop between BASL and the mitogen-activated protein kinase (MAPK) pathway is essential for enforcing different cell fates after ACD (Zhang et al, 2015).…”
mentioning
confidence: 99%
“…In monocots, where stomata develop in rows flanking parallel veins, once the stomatal cell file is established, cells divide asymmetrically to form a larger interstomatal sister cell and a GMC ( Stebbins and Shah, 1960 ; McKown and Bergmann, 2020 ; Nunes et al, 2020 ). In both cases, once established, the GMC differentiates and divides symmetrically into the stomatal guard cell pair ( Conklin et al, 2019 ; McKown and Bergmann, 2020 ; Nunes et al, 2020 ; Guo et al, 2021 ). Consistent with its role in asymmetric cell divisions in root development, it has been suggested that SCR may be required for stomatal patterning in rice ( Kamiya et al, 2003 ; Wu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%